WEB-BLOG TO ENCOURAGES WRITING SKILL - Moh Hafidz (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2020)
Writing is exploring some ideas in online media in academically texts . In this study, the researcher statistically examines Web-log to encourage Students' Writing Skills. This research uses quasi-experimental research designs with non-equivalent groups pretest-posttest. There are experimental and control group. these groups are given in different treatments. the experimental group is taught using Web-log media and the control group is textbook. The population of this research is eleventh grade students of SMAN Bangkalan in the. The number of subjects was 46 students. Data obtained by conducting essay writing tests (pre and post tests) in class XI- 4 (experimental) and class XI- 5 (control group). The result of test are analyzed by using covariate analysis (ANCOVA). The results show that the P-value score (0.16) <0.05 (alpha). It means that the hypothesis (H0) is rejected and (Ha) is accepted. from these results, there are significant differences in student grades. Therefore, the students who are taught using the Web-log on writing have better scores than students who are taught using textbook media, the most significant effect of Web-log media on writing skill is on the generic structure aspect.